Efficient narrowband green OLEDs with TADF sensitizers combining multiple charge-transfer pathways. (8th February 2023) - Li, Deli; Yang, Jiaji; Chen, Jiting; Peng, Xiaomei; Li, Wei; Chen, Zijian; Qiu, Weidong; Yang, Guo-Xi; Yang, Zhihai; Li, Mengke; Jiang, Simin; Liu, Denghui; et al.
Abstract : Benefitting from the concurrent intramolecular TBCT and TSCT of ortho -linked TADF materials, high k F and k RISC are achieved simultaneously and the devices using o -DCz-TRZ and BN-DMAc as emitters achieved high EQEs of 20.3% and 24.2%. Abstract : Multiple resonance (MR) thermally activated delayed fluorescence (TADF) emitters have attracted much attention for their narrow emission band and high efficiency. However, organic light-emitting devices based on MR-TADF emitters generally suffer from severe efficiency roll-off at high current density due to their relatively large singlet–triplet splitting energy. In this work, three TADF molecules are designed by an ortho -connected oligo carbazole donor and diphenyltriazine acceptor with the purpose of combining both through-bond charge transfer (TBCT) and through-space charge transfer (TSCT). Through fine tuning the proportion of intramolecular TBCT and TSCT by changing the number of carbazole units, a relatively high reverse intersystem crossing rate ( k RISC ) approaching 10 6 s −1 and radiative transition rate ( k F ) of over 10 6 s −1 are achieved. As a result, the devices using these molecules as emitters give maximum external quantum efficiency (EQE) of over 20% with extremely low efficiency roll-off of 9.9% at the practical luminance of 1000 cd m −2 . Furthermore, by using these materials as assistant hosts and sensitizers and DMAc-BN as a terminal emitter, high efficiencies of 23.9% and 66.0 lm W −1 are achieved with a full width at half maximum of 46 nm, featuring slow efficiency roll-off with EQE of 17.9% at the luminance of 1000 cd m −2 .